Competitive interaction and economic damage level of ryegrass harmfulg in canola hybrids - Galon, Leandro; Franceschetti, Milena Barretta; Portes, Juliane Cervi; Toso, Janaíne Oliveira; Brunetto, Leonardo; Menegat, André Dalponte; Müller, Caroline; Perin, Gismael Francisco (Revista de Ciências Agroveterinárias, 2023)
In canola, yield and grain quality losses occur due to the interference caused by ryegrass (Lolium multiflorum) when infesting the crop. Thus, the objective was to evaluate the interference and identify explanatory variables seeking to determine the level of economic damage (NDE) of different densities of ryegrass infesting canola hybrids. The experiment was carried out in a randomized block design, with one replication. The treatments consisted of five canola hybrids (Hyola 433, Hyola 61, Alht B4, Hyola 575 CL and Hyola 76) and 12 ryegrass densities, from 0 to 260 plants m-2, in competition with the crop. At 50 days after plant emergence, the variables as plant densities, leaf area, soil cover and shoot dry matter of ryegrass plants were evaluated. Grain yield, control cost, grain price and control efficiency were determined in canola plants. The soil cover presented the best fit to the rectangular hyperbola model, adequately estimating the grain yield losses due to ryegrass interference. The canola hybrids Hyola 433 and Hyola 575 CL were the most competitive when compared to the others in the presence of the competitor, with higher values of EDL. The canola hybrids Hyola 433 and Hyola 575 CL showed the highest EDL values with 3.85 to 5.13 plants m-2 in all simulations performed, respectively. The lowest EDL values were obtained with hybrids Hyola 61, Alht B4 and Hyola 76 with average variations of 1.02 to 2.15 plants m-2, respectively. The canola grain yield, grain bag price, efficiency of the herbicide, and the reduction in the control cost cause variation in the economic damage level values.